To six ports we have arrived, with the good winds of a symposium - Campaña, Andrea (Árboles y Rizomas, 2021)
The journal’s editor and main coordinator reflect on the political times in which this new issue of the journal is presented, they make a brief review of the symposium that was organized to socialize the journal, and introduce the contents of Volume III, Number 2 of Arboles y Rizomas.